Strategi Manajemen Pendidikan dalam Pengelolaan Pusat Kegiatan Belajar Masyarakat Baiturrahman Depok - Manaf, Abdul (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to analyze the education management strategy in the management of the Baiturrahman Depok Community Learning Center (PKBM). PKBM acts as a non-formal educational institution that provides various learning programs such as equivalency education, work skills, and community empowerment. Effective PKBM management requires a comprehensive management strategy to ensure the sustainability and quality of the programs provided. This method uses qualitative research with a case study approach. Data were collected through in-depth interviews, observations, and documentation of PKBM activities. The results of the study indicate that PKBM Baiturrahman implements a management strategy that includes planning, organizing, implementing, and supervising. At the planning stage, the main focus is to design programs that are in accordance with the needs of the surrounding community, including equivalency education programs and skills training. Organization involves cooperation between PKBM managers, tutors, and volunteers who coordinate with each other to support program implementation. The implementation of activities is carried out with a participatory approach, where participants are encouraged to be actively involved in the learning process.